(untitled) (Texas Journal of Engineering and Technology, 2023)
This article presents the problems associated with determining the combat capability of the personnel of military units in peacetime and ways to solve them, as well as models for determining the combat capability of the personnel of military units. A technique for accurate assessment of the level of combat readiness of the personnel of military units in peacetime is given. Methods for determining the quality index of the combat capability of the personnel of military units are analyzed. Indicators that determine the combat capability of personnel have been formed. The assessment of the capabilities of military units explores the problems of data processing in information environments.